Cellulose nanocrystals and zinc oxide in pineapple starch films for enhanced banana shelf-life - Lanhao, Li; Siew, Xian Chin; Pornchai Rachtanapun; Taweechai Amornsakchai; Poi, Sim Khiew; Shahariar Chowdhury; Sarani Zakaria; Chin, Hua Chia (Penerbit Universiti Kebangsaan Malaysia, 2025)
This study investigates the development of biodegradable films from pineapple stem starch enhanced with cellulose nanocrystals (CNC) and zinc oxide (ZnO) nanoparticles for improved food preservation. The film-forming behavior of pineapple stem starch was examined with varying concentrations of glycerol (0-30%), CNC (0-1.5%), and ZnO (0-20%). Rheological measurements showed that glycerol concentrations significantly influenced the viscoelastic properties of the starch solutions, with a notable peak in viscosity observed at 20% glycerol. The addition of CNC increased the storage modulus (G’) and viscosity of the starch solutions, indicating enhanced structural integrity. ZnO nanoparticles imparted effective UV-blocking capabilities to the films, with optimal performance observed at 10% concentration. Water vapor permeability (WVP) of the films slightly increased with ZnO content, ranging from 0.0127 to 0.0157 g·m⁻¹·h⁻¹·Pa⁻¹. Scanning electron microscopy (SEM) analysis showed uniform dispersion of ZnO nanoparticles within the starch matrix. The ZnO-enhanced starch coatings effectively extended the shelf life of bananas by delaying the ripening process. This study demonstrates the potential of pineapple stem starch-based films enhanced with CNC and ZnO as a sustainable and effective solution for food packaging, contributing to reduced food waste and environmental impact.